(untitled) (Baghdad Science Journal, 2014)
Kombucha(Khubdat Humza) is composed of yeast and acetic acid bacteria especially, Acetobacter xylinum which forms a cellulose pellicle on tea broth. Kombucha(Khubdat Humza) produces bacterial cellulose pellicles, with unique purity and fine structure. It can be used in many forms, such as an emulsifier, stabilizer, dispersing agent, thickener and gelling agent but these are generally subsidiary to its most important use of holding on to water. Recently, bacterial cellulose is used in many special applications such as a scaffold for tissue engineering of cartilages and blood vessels, also for artificial skin for temporary covering of wounds, as well as its used in the clothing industry. The yield of cellulose produced were investigated in this study, the tea broth was fermented naturally over a period of up to 20 days in the presence of different amounts of black tea and sucrose as nitrogen and carbon sources. 10g/L black tea produced highest weight of bacterial cellulose (55.46g/L) and 100g/L sucrose also exhibited high amount of pellicle (63.58g/L). Temperature was essential factor on growth, where the pellicle was formed at range (20°C - 50°C) and higher temperature over 50°C depressed the bacterial cellulose formation. The bacterial cellulose production increased with the increase of surface area and depth of the broth. Findings from this study suggest that the yield of cellulose depends on many factors that need to be optimized to achieve maximum yield.